2008 21st IEEE International Symposium on Computer-Based Medical Systems 2008
DOI: 10.1109/cbms.2008.15
|View full text |Cite
|
Sign up to set email alerts
|

Automated Detection of Optic Disc Location in Retinal Images

Abstract: This contribution presents an automated method to locate the optic disc in color fundus images. The method uses texture descriptors and a regression based method in order to determine the best circle that fits the optic disc. The best circle is chosen from a set of circles determined with an innovative\ud method, not using the Hough transform as past approaches. An evaluation of the proposed method has been done using a database of 40 images. On this data set, our method achieved 95% success rate for the local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…The next step in our method is to detect the optic disk, and remove it from the f 5 image. Despite the fact that several methods have been proposed in the literature for detecting the optic disk (see Seo et al [19], Kande et al [20] and Lupaş cu et al [21]), we have developed our own morphological method for detecting the optic disk because of its adequacy to our present needs, but the above mentioned methods also could be adopted. Our approach to detect the optic disk relies on mathematical morphology techniques, and has two main stages, namely: (1) detection of the optic disk location; (2) detection of the optic disk boundary.…”
Section: Stage A: Coarse Detection Of Exudatesmentioning
confidence: 98%
“…The next step in our method is to detect the optic disk, and remove it from the f 5 image. Despite the fact that several methods have been proposed in the literature for detecting the optic disk (see Seo et al [19], Kande et al [20] and Lupaş cu et al [21]), we have developed our own morphological method for detecting the optic disk because of its adequacy to our present needs, but the above mentioned methods also could be adopted. Our approach to detect the optic disk relies on mathematical morphology techniques, and has two main stages, namely: (1) detection of the optic disk location; (2) detection of the optic disk boundary.…”
Section: Stage A: Coarse Detection Of Exudatesmentioning
confidence: 98%
“…The second one is specialized in vessel extraction and publishes two sets of images, one for training, showing the segmentation of their corresponding vessels network, and one for testing purposes, in which two segmentations of retinal vessels can be observed. Both of them have been referenced in numerous studies [17,18].…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, for the pictures with less than 5 pixel of uncertainty, a success ratio of 96 % was reported for the identification of the contours of the optic disc; these results were based on tests performed on 110 images. Lupascu et al [16] identified the geometric location and contours of the optic disc. This study reported optic disc detection success rate of 95 % and an optic disc contour extraction success rate of 70 %.…”
Section: Introductionmentioning
confidence: 99%
“…Also, recorded required time for the detection of the optic disc in these images is 2.13 s for DRIVE dataset, 2.81 s for STARE dataset, and 3.52 s images. Therefore, development of automatic systems is quite important [3,8,16,19,27,29]. When retinal images are controlled automatically by the system, they can be examined and diagnosed by professional physicians when any suspicion of disease is encountered by the automatic control.…”
Section: Introductionmentioning
confidence: 99%